Unraveling Reticulate Evolution in Opuntia (Cactaceae) From Southern Mexico - Granados-Aguilar, Xochitl; Granados Mendoza, Carolina; Cervantes, Cristian Rafael; Montes, José Rubén; Arias, Salvador (Frontiers in Plant Science, 2021)
The process of hybridization occurs in approximately 40% of vascular plants, and this exchange of genetic material between non conspecific individuals occurs unequally among plant lineages, being more frequent in certain groups such as Opuntia (Cactaceae). This genus is known for multiple taxonomic controversies due to the widespread polyploidy condition and probable hybrid origin of several of its species. Members of this genus in southern Mexico have been poorly studied despite their great diversity in regions such as the Tehuacán-Cuicatlán Valley with almost 12% of recognized native species in Mexico. In this work, we focus on testing the hybrid status of two putative hybrids from this region, Opuntia tehuacana and Opuntia pilifera, and estimate if hybridization occurs among southern opuntias using two new nuclear intron markers to construct phylogenetic networks in PhyloNet and perform invariant analysis under the coalescent model with HyDe. For the test of hybrid origin in O. tehuacana, our results could not recover hybridization as proposed in the literature, but we found introgression into O. tehuacana individuals involving O. decumbens and O. huajuapensis. Regarding O. pilifera, we identified O. lasiacantha and O. velutina as probable parental species, but we could not confirm this assumption due to the reduced number of loci and the need to include more species from the Nopalea and Basilares clades. Finally, we suggest new hybridization and introgression cases among southern Mexican species involving O. tehuantepecana and O. depressa as parental species of O. velutina and O. decumbens.